The Efficacy of an Alternative Instructional Programme Designed to Enhance Secondary Students' Competence in the Triplet Relationship - Treagust, David; Chandrasegaran, Chandra (Springer, 2009)
Research has consistently shown that secondary school students have conceptual difficulties transferring between macroscopic, submicroscopic and symbolic representations in chemistry. In this chapter, we describe how students responded to a 15-item two-tier multiple choice diagnostic instrument that analysed their understanding of seven types of chemical reactions using macroscopic, submicroscopic and symbolic representations after they had been taught a special alternative programme to make these three representations more overt. The research has shown that by placing particular emphasis on the triplet relationship of macroscopic, submicroscopic and symbolic representations in chemistry, it is possible for students to achieve more meaningful learning of chemical representations. Suggestions are made for how such improved learning can be accommodated in normal classrooms, as compared to research-oriented classrooms.